Applying the core microbiome to understand host–microbe systems. Issue 7 (14th April 2020) - Risely, Alice
Abstract: The host‐associated core microbiome was originally coined to refer to common groups of microbes or genes that were likely to be particularly important for host biological function. However, the term has evolved to encompass variable definitions across studies, often identifying key microbes with respect to their spatial distribution, temporal stability or ecological influence, as well as their contribution to host function and fitness. A major barrier to reaching a consensus over how to define the core microbiome and its relevance to biological, ecological and evolutionary theory is a lack of precise terminology and associated definitions, as well the persistent association of the core microbiome with host function. Common, temporal and ecological core microbiomes can together generate insights into ecological processes that act independently of host function, while functional and host‐adapted cores distinguish between facultative and near‐obligate symbionts that differ in their effects on host fitness. This commentary summarizes five broad definitions of the core microbiome that have been applied across the literature, highlighting their strengths and limitations for advancing our understanding of host–microbe systems, noting where they are likely to overlap, and discussing their potential relevance to host function and fitness. No one definition of the core microbiome is likely to capture the range of key microbes across a host population. Applied together, they have the potential to reveal different layers of microbial organization from which we can begin to understand the ecological and evolutionary processes that govern host–microbe interactions. Abstract : Researchers of host‐associated microbiomes often want to identify key microbes out of the hundreds or thousands that make up the microbial community. These key microbes have traditionally been termed the 'core microbiome', yet the core microbiome can be split into five conceptually distinct definitions, and not all are necessarily linked to host function.